Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.5530/pc.2015.4.5
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic and behavior effect of the ethanolic extract from the bark of Maytenus macrocarpa (Ruiz &Pav.) Briq.in mice

Abstract: Antipsychotic and behavior effect of the ethanolic extract from the bark of Maytenus macrocarpa (Ruiz &Pav.) Briq.in mice ABSTRACTIntroduction: Different studies indicate that Maytenus has many effects and that M. obtusifolia species has a central nervous system depressant effect. Objective: To determine antipsychotic and behavior modifying effect of the Maytenus macrocarpa (Ruiz & Pav.) Briq.ethanolic extract, using the forced swim test and Irwin test. Method: 77 albino mice were used, with an average weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…[10][11][12][13] Also, there is a study in rodents of the bark of Maytenus macrocarpa in which it was demonstrated neuroleptic effect, sedation and stereotypes, on the other hand, in another study of the root of Maytenus obtusifolia it was demonstrated the potential depressant effect over the central nervous system. [14][15] Depression is a disorder of the mood that causes disability and affects more than 300 million people around the world. In Peru the prevalence of depression is at the range of 18, 2% to 21, 4%.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Also, there is a study in rodents of the bark of Maytenus macrocarpa in which it was demonstrated neuroleptic effect, sedation and stereotypes, on the other hand, in another study of the root of Maytenus obtusifolia it was demonstrated the potential depressant effect over the central nervous system. [14][15] Depression is a disorder of the mood that causes disability and affects more than 300 million people around the world. In Peru the prevalence of depression is at the range of 18, 2% to 21, 4%.…”
Section: Introductionmentioning
confidence: 99%